Bahasa Isyarat dan Juru Bahasa Isyarat: Perkembangan dan Isu - Rachmawati, Raja (Kementerian Sekretariat Negara Republik Indonesia, 2020)
This article discusses about sign language and sign language interpreter in Indonesia. The objective of this article is to explore the development and issue of sign language and sign language interpreter. This article employs descriptive qualitative method with library research approach. The result of the study shows that the main issue of sign language in Indonesia is a conflict that occurred due to government policies regarding the establishment of the Sistem Bahasa Isyarat Indonesia (SIBI) in the formal environment which is recognized as a sign language for deaf people in Indonesia. Another issue is about the number of sign language interpreters that are few or there is a dearth of sign language interpreters in Indonesia. Meanwhile, sign language interpreters play important roles in order to help Deaf people to get more information and knowledge in various fields of life and to express their thought and feeling that cannot be delivered directly. Keywords : Tuli, bahasa isyarat, juru bahasa isyarat Tuli, isu.